2020
DOI: 10.1634/theoncologist.2019-0797
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Relapse Risk (CERR) Score for Colorectal Liver Metastases: Development and Validation

Abstract: Background The calculation of the tumor burden score (TBS) is not perfect because the bilobar spread of colorectal liver metastasis (CRLM) is neglected. The identification of an ideal prognostic scoring system for CRLM remains controversial. Materials and Methods Patients who underwent curative intent liver resection for CRLM from one medical center were enrolled in cohort 1 (787 patients) and cohort 2 (162 patients). Tumor relapse‐free survival (RFS) was the main outcome. A Cox regression model was used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
(58 reference statements)
0
33
0
Order By: Relevance
“…These extracted quantitative data reflect the crucial part of the establishment of radiomics prediction models. In practice, 50 to 5,000 radiomic features processed by specific software, including PyRadiomics ( 32 , 33 ), CERR ( 34 , 35 ) or IBEX ( 36 , 37 ), are usually divided into morphological, intensity-based, and dynamic features ( 14 ) ( Figure 2 ). Morphology-based features can collect three-dimensional (3D) shape characteristics, including volume, surface area, and sphericity.…”
Section: Development Of Radiomics Prediction Modelsmentioning
confidence: 99%
“…These extracted quantitative data reflect the crucial part of the establishment of radiomics prediction models. In practice, 50 to 5,000 radiomic features processed by specific software, including PyRadiomics ( 32 , 33 ), CERR ( 34 , 35 ) or IBEX ( 36 , 37 ), are usually divided into morphological, intensity-based, and dynamic features ( 14 ) ( Figure 2 ). Morphology-based features can collect three-dimensional (3D) shape characteristics, including volume, surface area, and sphericity.…”
Section: Development Of Radiomics Prediction Modelsmentioning
confidence: 99%
“…This study also constructed novel nomograms for the prediction of survival. Some nomograms have been developed to predict individual survival probabilities for patients with CRLM undergoing liver resection (7,8). However, the nomograms developed here have the following specific advantages.…”
Section: Nomogram For Os Predictionmentioning
confidence: 99%
“…Nomograms incorporating and illustrating important prognostic factors have been widely used as reliable tools for predicting survival probabilities for individual patients. Chen et al (7) established a comprehensive evaluation of relapse risk score based on KRAS status, primary node status, extrahepatic disease, carcinoembryonic antigen (CEA) level, and tumour burden score to predict the prognosis of patients with CRLM. Liu et al (8) revealed that a nomogram constructed according to tumour size, liver metastasis number, RAS mutation status, and primary lymph node metastasis has a favorable calibration and C-index for predicting survival in patients with CRLM.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor biology including chemosensitivity can facilitate subsequent treatment strategies. Several scoring systems were developed to predict the recurrence and prognosis in CLM [ 7 , 8 , 9 ]. Previous scoring systems included disease-free interval, the size and number of LM, the staging of tumor and node, the level of carcinoembryonic antigen (CEA), tumor grade, margin status and age [ 7 , 8 , 9 ].…”
Section: Patient Selection For Hepatic Resection and Scoring In Colorectal Liver Metastasesmentioning
confidence: 99%
“…Several scoring systems were developed to predict the recurrence and prognosis in CLM [ 7 , 8 , 9 ]. Previous scoring systems included disease-free interval, the size and number of LM, the staging of tumor and node, the level of carcinoembryonic antigen (CEA), tumor grade, margin status and age [ 7 , 8 , 9 ]. Fong et al suggested five clinical criteria as a clinical risk score including nodal involvement, DFS from the primary to LM < 12 months, number of LM > 1, CEA > 200 ng/mL, the largest tumor >5 cm [ 8 ].…”
Section: Patient Selection For Hepatic Resection and Scoring In Colorectal Liver Metastasesmentioning
confidence: 99%